2016
DOI: 10.3390/agronomy6020033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Anthesis Water Deficit on Yield and Yield Components in Barley (Hordeum vulgare L.) Plants Grown under Controlled Conditions

Abstract: Drought at pre-anthesis stages can influence barley growth and results in yield losses. Therefore, it is important to understand how drought at pre-anthesis can affect different traits associated with yield reduction in barley. The objective of this study was to understand the relevance of the genetic background of major flowering time genes in barley plants subjected to pre-anthesis drought and its impact on yield and yield components. A glasshouse experiment using a Randomized Complete Block Design was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 41 publications
8
43
0
Order By: Relevance
“…We observed a trend that late plant development (Table 2). Here, elevated temperatures and low rainfall restricted plant growth to a few months and thus earliness is a major breeding goal 48,49 . In future, this situation may intensify, since climate change is expected to further shorten the growing period in drought and heat prone locations like in Jordan 26,32,50 .…”
Section: Grain Yield Correlations Indicate That Yield Formation Depenmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a trend that late plant development (Table 2). Here, elevated temperatures and low rainfall restricted plant growth to a few months and thus earliness is a major breeding goal 48,49 . In future, this situation may intensify, since climate change is expected to further shorten the growing period in drought and heat prone locations like in Jordan 26,32,50 .…”
Section: Grain Yield Correlations Indicate That Yield Formation Depenmentioning
confidence: 99%
“…In those areas where drought and heat affect plant development and grain maturation, early maturing lines like HEB_05_043, HEB_15_082 or HEB_10_173 may be beneficial because of their fast development ( Figure 5; Supplementary Figure S9; Supplementary Table S10a). Moreover, the increased tiller capacity of HEB-YIELD lines may be promising to achieve an improved canopy cover, reducing moisture losses 26,49 and to increase biomass yield. The latter trait may be high value in the eastern part of the Mediterranean basin where straw and grains of barley are mainly used for animal feeding 91,92 .…”
Section: The Best Wild Barley Heb-yield Lines Match the Yield Performmentioning
confidence: 99%
“…In Jordan, water deficit is the most limiting factor for wheat yield in most years [13]. The unfavorable distribution of rain over the growing season and the year-to-year fluctuations constitute a major constraint to wheat growth and yield [50][51][52][53][54].…”
Section: Climatic Conditionsmentioning
confidence: 99%
“…Such models have also predicted an increase of 3-5 • C in temperature [11] and around a 20% loss in soil moisture [12], supported by the fact that wheat production suffered from yield variability from year to year and from one location to another, caused by drought stress. Drought may occur pre-anthesis and negatively affect crop establishment and floret fertility [13,14] or post-anthesis and adversely affect grain filling and grain development [15]. Therefore, improvement of wheat productivity under drought conditions became the main objective of the current breeding programs in arid and semi-arid regions.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Al-Ajlouni et al (2016) showed a huge impact of pre-anthesis water deficit on barley yield components due to water deficit stress during tillering and stem elongation stages, whereas in the Mediterranean zone cereal crops are exposed to frequent post-anthesis water deficit. Our results indicate that water deficit stress affects yield components to varying degrees, according to the development stages.…”
Section: Discussionmentioning
confidence: 99%